Performance of a Horizontal Double Cylinder Type of Fresh Coffee Cherries Pulping Machine - Sukrisno Widyotomo; Sri Mulato; H Ahmad; s Soekarno (Indonesian Coffee and Cocoa Research Institute, 2009)
Pulping is one important step in wet coffee processing method. Usually, pulping process uses a machine which constructed using wood or metal materials. A horizontal single cylinder type coffee pulping machine is the most popular machine in coffee processor and market. One of the weakness of a horizontal single cylinder type coffee pulping machine is high of broken beans. Broken beans is one of major aspect in defect system that result in low quality. Indonesian Coffee and Cocoa Research Institute has designed and tested a horizontal double cylinder type coffee pulping machine. Material tested is Robusta cherry, mature, 60—65% (wet basis) moisture content, which size compostition of coffee cherries was 50.8% more than 15 mm diameter, 32% more than 10 mm diameter, and 16.6% to get through 10 mm hole diameter; 690—695 kg/m3 bulk density, and clean from methal and foreign materials. The result showed that this machine has 420 kg/h optimal capacity in operational conditions, 1400 rpm rotor rotation speed for unsorted coffee cherries with composition 53.08% whole parchment coffee, 16.92% broken beans, and 30% beans in the wet skin. For small size coffee cherries, 603 kg/h optimal capacity in operational conditions, 1600 rpm rotor rotation speed with composition 51.30% whole parchment coffee, 12.59% broken beans, and 36.1% beans in the wet skin. Finally, for medium size coffee cherries, 564 kg/h optimal capacity in operational conditions, 1800 rpm rotor rotation speed with composition 48.64% whole parchment coffee, 18.5% broken beans, and 32.86% beans in the wet skin.Key words : coffee, pulp, pulper, cylinder, quality.